Brazil : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2019)
This Selected Issues paper examines the profitability of the foreign exchange (FX) swaps issued the Central Bank of Brazil (BCB) between May 2013 and February 2019 to shed light on the rationale for FX intervention. Using interest rate and exchange rate forecasts, the paper shows that that FX swaps have been profitable in expectation, even though actual returns were negative due to unexpected exchange rate depreciations. Moreover, the scale of FX intervention is correlated with the expected profitability of the swaps, further suggesting that the BCB used FX intervention to stem abnormal movements of the exchange rate. Despite being profitable in expectation, swaps incurred realized losses due to unexpected exchange rate depreciations. The analysis suggests that the BCB used FX intervention to lean against temporary excessive movements of the exchange rate. The expected profitability of FX swaps can be monitored in real time and may thus provide guidance on the appropriate level of intervention.